Brochure on forage production (Establishment management, harvest) - Ohmstedt, Uwe (Bioversity International and the International Center for Tropical Agriculture, 2021)
Feeding of livestock is a critical point in all livestock production. Proper feeding is influencing livestock’s development, health, productivity and reproduction rate. This applies for all sectors of livestock keeping. Of course, also other factors like genetics, health care, animal welfare etc also influence the performance of cows, but even if all these elements are well respected, feeding will be the determining element for reaching out to the dairy cows’ potential. It is a well known fact, that many dairy cows are underfed in quantity and quality. This leads to under performing cows and makes dairy farming less economic.